IMPLEMENTASI PROGRAM KELUARGA HARAPAN SEBAGAI INSTRUMEN KEBIJAKAN PUBLIK DALAM MENGURANGI KEMISKINAN - Rahmita Febi Nuraini; Nadila Rizki Auliya; Indah Prabawati; Wilda Sumarsyah (Jurnal Kebijakan Pembangunan Daerah, 2026)
Poverty as a multidimensional problem, is a fundamental challenge to development, necessitating policies that go beyond temporary assistance and strengthen the quality of human resources. The Indonesian government has implemented the Family Hope Program (PKH) as a form of conditional social protection. This study aims to analyze the implementation of PKH as a public policy tool to reduce poverty and identify factors influencing its effectiveness. The study employed a Systematic Literature Review (SLR) method with a descriptive qualitative approach through an examination of various related scientific articles. The findings indicate that PKH contributes significantly to improving the welfare of the poor, particularly in education and health, and serves as a social safety net during crises. However, its effective implementation remains hampered by communication, resources, disposition, and bureaucratic structure. The main obstacles identified are inaccurate targeting of beneficiaries, limited capacity of facilitators, and weak inter-agency coordination. Therefore, PKH is an effective short-term policy, but requires improved governance and integration with economic empowerment programs to achieve sustainable poverty alleviation. This research contributes to the enrichment of public policy implementation studies through a synthesis of literature findings